Short-time effect of the kangaroo position on electromyographic activity of premature infants: a randomized clinical trial - Kaísa Trovão Diniz; José Eulálio Cabral Filho; Rafael Moura Miranda; Geisy Maria Souza Lima; Natália Priscila dos Santos Figueredo; Kalline Fernanda Nunes de Araújo (Elsevier, 2020)
Objective: To verify the short-term influence of the kangaroo position (KP) on the electromyography activity of preterm newborns. Method: A clinical study was conducted in a kangaroo unit sector (secondary and tertiary care) in the city of Recife, Brazil, with 44 preterm infants randomized to intervention (n = 21) and control (n = 23) groups. The KP was performed through a band that supports the newborn against the adult's thorax, in a prone and vertical position, and infants were dressed with few pieces of clothes, thus keeping skin-to-skin contact with the mother. Surface electromyography was used to investigate the muscle activity of the biceps brachii and hamstrings. The randomization of the groups was performed by the program R® (v. 3.3.1). The electromyography registrations were made at three different times: before the KP and after one and two hours of KP. In the control group, the registrations were performed at the times corresponding to those of the intervention group. The mean values of the electromyography activity among the times were analyzed by ANOVA for repeated measures and the Kruskal-Wallis test. The clinical trial was recorded in ClinicalTrials.gov (NCT02849665 - 07/28/2016). Results: In the intervention group (n = 21), there was a variation of the electromyography activity values between the three recording moments for both the biceps brachii and hamstrings. In the control group (n = 23), there was no statistical difference between the recording moments for both. Conclusions: The KP increases the short-term electromyographic activity of the biceps brachii and hamstrings. Resumo: Objetivo: Verificar a influência de curto prazo da Posição Canguru (PC) sobre a atividade eletromiográfica de recém-nascidos prematuros. Método: Foi feito um estudo clínico em um setor da Unidade do Método Mãe Canguru (cuidado secundário e terciário) na cidade de Recife, com 44 neonatos prematuros randomizados em grupos de Intervenção (n = 21) e Controle (n = 23). A Posição Canguru foi feita por meio de uma faixa que apoia o recém-nascido de bruços contra o tórax do adulto, na posição vertical e vestido com poucas peças de roupa, mantém o contato pele a pele com a mãe. Foi usada a Eletromiografia Superficial para investigar a atividade muscular dos bíceps braquiais e músculos isquitobiais. A randomização dos grupos feita com o software R (versão 3.3.1)®. Os registros da eletromiografia foram feitos em três momentos: antes da PC e após uma e duas horas da Posição Canguru. No Grupo de Controle, os registros foram feitos nos momentos correspondentes àqueles do Grupo do Método Mãe Canguru. Os valores médios da atividade eletromiográfica entre esses momentos foram analisados pela análise de variância (Anova) de medidas repetidas e por um teste de Kruskal-Wallis. O ensaio clínico foi registrado no Clinical Trials (NCT02849665 - 28/07/2016). Resultados: No Grupo do Método Mãe Canguru (n = 21), houve variação dos valores da atividade eletromiográfica entre os três momentos de registro de atividade dos bíceps braquiais e dos músculos isquitobiais. No Grupo de Controle (n = 23), não houve diferença estatística entre os momentos de registro. Conclusões: A PC aumenta a atividade eletromiográfica de curto prazo dos músculos bíceps braquiais e isquitobiais.